If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (18z + 9)(3y * 7) = 6 Reorder the terms: (9 + 18z)(3y * 7) = 6 Reorder the terms for easier multiplication: (9 + 18z)(3 * 7y) = 6 Multiply 3 * 7 (9 + 18z)(21y) = 6 Remove parenthesis around (21y) (9 + 18z) * 21y = 6 Reorder the terms for easier multiplication: 21y(9 + 18z) = 6 (9 * 21y + 18z * 21y) = 6 (189y + 378yz) = 6 Solving 189y + 378yz = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Reorder the terms: -6 + 189y + 378yz = 6 + -6 Combine like terms: 6 + -6 = 0 -6 + 189y + 378yz = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-2 + 63y + 126yz) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-2 + 63y + 126yz)' equal to zero and attempt to solve: Simplifying -2 + 63y + 126yz = 0 Solving -2 + 63y + 126yz = 0 Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 63y + 2 + 126yz = 0 + 2 Reorder the terms: -2 + 2 + 63y + 126yz = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 63y + 126yz = 0 + 2 63y + 126yz = 0 + 2 Combine like terms: 0 + 2 = 2 63y + 126yz = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -103=2x+7 | | 33=3x-12 | | 3(x+6)=90 | | -9x+4=22 | | 5x+11=71 | | 4x+6=8x+1 | | R-4/8=7 | | 2+8x+15=6x-11+2x | | 4x+18=7x-5+12-7 | | N/-9=7 | | 15x-4=x+8 | | 4/-8=16 | | (x+9)/(2x+14)*(8x+56)/(9x+81) | | -8=2+5x | | (8x+56)/(9x+81) | | 5x-4(x-5)=-2 | | 3(2p+7)=8(-2t+11) | | 38=2x+10 | | 45-10+7x-3x=8x+2x-9+20 | | 16x^4-17x^2+1=0 | | 5x+6=8x-2 | | x/4+1=x/3+5 | | (4u-6)(7-u)=0 | | 8x+56/9x+81 | | x^2+y^2-6x+18y+100=0 | | x^2+y^2-6x+18y+91=0 | | 2x+8=5x-10 | | x^2+y^2-6x+18y+89=0 | | x^2+y^2-6x+18y+90=0 | | n/5=19 | | B/3+7 | | -2=r-19 |